PERKUATAN BANGUNAN EKSISTING AKIBAT TERJADINYA DIFFERENTIAL SETTLEMENT PADA PONDASI - Tarigan, Valentana Ardian; Panggabean, Immanuel Panusunan Tua; Laia, Fiber (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2024)
Differential settlements of foundations in buildings often results in building damage. The first damage appears on the architectural part and then as the difference in settlement increases, it will start to attack the structural part. This increase certainly results in harm to building users. Buildings that use shallow foundations can generally be divided into causes based on soil parameters, soil load on the foundation and the cross-sectional shape of the foundation. Shallow foundations according to Terzaghi, the soil parameters that influence them are the coefficient of cohesion and friction angle plus the specific gravity of the soil which supports the load coming from the building. The foundation cross-section factor is influenced by the depth and width of the cross-section whether it is square, round or continuous. The oblique crack pattern that occurs in the building walls is an indication of differences in settlement in the foundation. This research was carried out by carrying out crack patterns that indicate foundation settlement, analyzing the causes of foundation settlement, and carrying out calculation analysis to determine the strengthening method. The method is carried out by collecting data on the dimensions of the building structure and compiling the parameters used according to loading regulations. The decline was caused by new embankments which were directly loaded and primary consolidation had not been completed, low soil bearing capacity in the surface layer, additional load from the design load.